The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13744-016-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine Alkaloids Negatively Affect a Generalist Herbivore Feeding on the Chemically Protected Legume Crotalaria pallida

Abstract: Plant secondary metabolites can have opposing effects on adapted specialist and non-adapted, generalist herbivores. In this study, we used Heliothis virescens (Fabricius) (Lepidoptera: Noctuidae) as a generalist, non-adapted model herbivore to test the possible effects of Crotalaria pallida (Fabaceae: Papilionoideae) defenses on herbivore performance. Neonate H. virescens larvae were able to consume C. pallida leaves and fruits and grow for a few instars, but none of them survived to pupation. We added isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Third, we do not know if the levels of PAs present in the field affect E. zinckenella . Previous studies showed that the negative effect of PAs on generalist herbivores depends on the concentration 70,71 . Forth, since C. pallida is an introduced species, it has not coevolved with these two herbivores for a long evolutionary time, and therefore may not be well adapted to avoid them 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we do not know if the levels of PAs present in the field affect E. zinckenella . Previous studies showed that the negative effect of PAs on generalist herbivores depends on the concentration 70,71 . Forth, since C. pallida is an introduced species, it has not coevolved with these two herbivores for a long evolutionary time, and therefore may not be well adapted to avoid them 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We expected that the specialist U. ornatrix would act as selection agent that decreases the concentration of PAs in natural populations, while the non-specialist E. zinckenella would act as a selection agent that increases the concentration of PAs. This expectation is based on the fact that PAs are known to deter generalist herbivores 16,17,70,71 , but have no negative effect on the specialist U. ornatrix 36 . U. ornatrix can sequester PAs and use them as defences against predators as well as a male pheromone 15,19,35,48,70,72 .…”
Section: Discussionmentioning
confidence: 99%
“…The content is in line with those reported by Govindappa et al (2011), by stating that the ethanol extract of C. pallida all parts of the plant contain alkaloids, flavonoids, tannins, steroids, terpenoids, saponins, and phenol. In addition it was reported also by Cogni and Trigo (2016) that has been isolated alkaloid from the leaf and fruit of C. pallida.…”
Section: Phytochemical Constituentsmentioning
confidence: 80%
“…Jb chemotype plants from the native populations contained, on average, 7.7% Er-like PAs, while in the introduced range, only trace amounts of erucifoline were present in this chemotype ( Figure 2 ), suggesting that erucifoline has been selected against. Several studies have shown that generalist insect herbivores respond differently to the same PA and that the relative effects of individual PAs can differ between herbivore species (Macel et al, 2005; Cheng et al, 2013; Wei et al, 2015; Cogni and Trigo, 2016). Thus, generalist herbivores, in turn, might play an important role in the evolution and maintenance of the diversity of PAs (Macel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%